Relationship between BRAF V600E and clinical features in papillary thyroid carcinoma - Yan, Changjiao; Huang, Meiling; Li, Xin; Wang, Ting; Ling, Rui (Endocrine Connections, 2019)
Objective To investigate the mutant status of BRAF gene and analyze its relationship to epidemiological risk factors and clinical outcomes among patients with papillary thyroid cancer (PTC) in the largest, single-institution Chinese cohort to date. Methods The medical records of 2048 PTC patients were reviewed in this retrospective study. Single-factor and multiple logistic regression analyses were applied to identify risk factors for BRAF V600E mutation. Survival outcomes including distant metastatic and persistent or recurrent PTC were examined, with a mean follow-up time of 23.4 (5–47) months. Results The BRAF V600E mutation was present in 83.7% of patients (1715 of 2048). Correlation was found between BRAF V600E mutation and several epidemiological features, including age, concomitant hypertension and Hashimoto thyroiditis (HT). For the clinicopathological features, BRAF V600E was significantly associated with bilateral multifocality (odds ratio (OR) 1.233, 95% confidence interval (CI) 1.063–1.431, P < 0.01) and less lateral lymph node metastases (OR 0.496, 95% CI 0.357–0.689, P < 0.01). Smaller tumor size and advanced disease stage were significant in single-factor analyses but became insignificant after multivariate adjustment. No association was found between BRAF V600E mutation and extrathyroidal invasion, distant metastatic and disease persistence or recurrence. Conclusion Part of epidemiological features are independent risk or protective factors for BRAF V600E mutation. The presence of BRAF V600E mutation is not an aggressive prognosis on poor clinical outcomes in PTC. However, the high prevalence of BRAF V600E may provide guidance for surgery strategy and opportunity for targeted treatment in recurrent and advanced stage disease.